2011
DOI: 10.1017/s1751731110001722
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite mapping of quantitative trait loci affecting meat quality, stress hormones and production traits in Duroc × Large White F2 pigs

Abstract: An F2 cross between Duroc and Large White pigs was carried out in order to detect quantitative trait loci (QTL) for 11 meat quality traits (L*, a* and b* Minolta coordinates and water-holding capacity (WHC) of two ham muscles, ultimate pH of two ham and one loin muscles), 13 production traits (birth weight, average daily gain during post-weaning and fattening periods, carcass fat depths at three locations, estimated lean meat content, carcass length and weights of five carcass cuts) and three stress hormone-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…A significant QTL was detected for birth weight on SSC10, where a QTL affecting the same trait was also reported at a similar position in a Duroc × Large White population [16]. This independent confirmation is noteworthy considering the low number of QTLs reported for this trait, and this result points to major-effect alleles (10% phenotypic variance in our population) segregating from Duroc and/or Large White breeds.…”
Section: Resultssupporting
confidence: 83%
“…A significant QTL was detected for birth weight on SSC10, where a QTL affecting the same trait was also reported at a similar position in a Duroc × Large White population [16]. This independent confirmation is noteworthy considering the low number of QTLs reported for this trait, and this result points to major-effect alleles (10% phenotypic variance in our population) segregating from Duroc and/or Large White breeds.…”
Section: Resultssupporting
confidence: 83%
“…The cDNA sequence analysis of parental strains revealed a Met276Ile mutation in WKY rat identical to that found in the Biobreeding rat strain that exhibits decreased CBG binding affinity for corticosterone (14). More recently, a series of studies conducted in different pig lines confirmed the genetic linkage or genetic association between SerpinA6/CBG locus and basal cortisol levels in pig (1518). Finally, in humans, a very significant association between the SERPINA6/SERPINA1 locus and morning plasma cortisol concentrations was reported in a genome-wide association meta-analysis using ~2.5 M SNPs in 12,597 Caucasian subjects, replicated in 2,795 participants (19).…”
Section: Genetic Studies Highlighting the Central Role Of Cbg In Gc Vmentioning
confidence: 86%
“…Later, a correlation between the percentage of fat and CBG binding capacity was replicated in a Meishan × Large White F10 intercross (21). However, no genetic linkage to body composition traits was detected in another pig study involving a different breed (Duroc instead of Meishan) (15). …”
Section: Genetic Studies Relating Cbg and Body Compositionmentioning
confidence: 96%
“…The QTL for cortisol level has been validated in an F2 Duroc × Large White population (Sanchez et al . ), Piétrain × (German Landrace × German Large White) crossbred (Ponsuksili et al . ), purebred Landrace (Okamura et al .…”
Section: Introductionmentioning
confidence: 99%